EFFECT OF BANK INDONESIA AND FEDERAL RESERVE SYSTEM RATE CHANGE POLICY TO BANKSâ STOCK IN INDONESIA - Arsyad, Ivolda
Stock market is affected by economic and political events, therefore creating sentimental issues that can affect the price and trading volume of the stock exchange. One of the economic events that are tested was monetary policy conducted by the central bank. Based on previous research conducted in various countries, it was said that monetary policy created impact on the return and trading volume of the banks’ stock. Therefore, this research was conducted to investigate if there is empirical evidence of an impact created by the monetary policy conducted by central bank to the banks’ stock in Indonesia. Method that was used in this research is event study methodology within 2 time frames, 5 days prior and after the events and 10 days prior and after the events. Samples used in this research are 5 most heavily traded bank’s stock in Indonesia which are Bank Mandiri, Bank Danamon, Bank Rakyat Indonesia, Bank Negara Indonesia, and Bank Central Asia. The events that are examined are: 1) Bank Indonesia raised the rate from 7.25% to 7.50% on November 12th 2013. 2) Bank Indonesia raised the rate from 7.50% to 7.75% on November 18th 2014. 3) Bank Indonesia reduced the rate from 7.75% to 7.50% on February 17th 2015. 4) The Fed raised the rate from 0%-0.25% to 0.25%-0.50% on December 17th 2015. Indicators that are used to measure the market reaction are the abnormal return and trading volume. The calculation shows mixed results. There is no significant difference in abnormal return with events related with the monetary policy conducted by The Fed and there is a significant decrease in average trading volume activity in 5 days period after The Fed raised the interest rate. There is only one result that shows significant difference in abnormal return, which is an increase in average abnormal return in 5 days period after Bank Indonesia increased the interest rate from 7.25% to 7.50% on November 12th 2013. There are no differences in average trading volume when Bank Indonesia raised the rate or decreased the rate.